Catalyzing Female Empowerment through Heritage Tourism: Propensity Score Matching Evidence from the Ulos Micro-Economy in North Sumatra - Indri Suryani Manik; Iis Sugandhi (Open Access Indonesia Journal of Social Sciences, 2025)
Heritage tourism has been theorized as a structural mechanism through which indigenous women artisans can advance their economic, social, and psychological standing, yet causal evidence anchored in counterfactual reasoning has remained scarce. This study quantified the impact of integration into the heritage tourism supply chain on the multidimensional empowerment of female Ulos weavers in North Sumatra, Indonesia. A cross-sectional observational design was applied to 450 women artisans (200 treated, 250 control) across three Ulos-producing districts. The 100-point Women’s Empowerment Index combined economic, social, and psychological sub-indices with adequate internal consistency (Cronbach’s alpha 0.83). Propensity score matching with a 0.05 caliper was used to construct a counterfactual based on age, education, marital status, dependents, weaving experience, and baseline wealth. After matching, 185 treated and 185 control units were retained, and the mean standardized bias declined from 28.3 percent to 3.2 percent. The Average Treatment Effect on the Treated indicated that tourism integration increased the overall empowerment score by 14.3 points (95% CI 10.18–18.42), the economic sub-index by 21.6 points, the social sub-index by 13.3 points, and the psychological sub-index by 8.0 points, with a monthly income premium of 1,450,000 IDR (all p < 0.01). Sensitivity analyses using kernel matching and inverse probability weighting yielded comparable results. Heritage tourism functioned as a measurable catalyst of multidimensional female empowerment among Ulos artisans. Strategic policy attention to direct market access, capacity building, and protection of indigenous designs is needed.